Investigate stakeholders’ perceptions of best practices of STEM education in the United Arab Emirates - MALAKA, SAWSAN (2018)
The United Arab Emirates (UAE) is in the transition from an oil-based to a knowledge-based economy. This shift requires a workforce that can develop 21st-Century Science, Technology, Engineering and Mathematics (STEM) skills. In order to make this transition and integrate with the global economy, the UAE must enhance the workforce channels concerned with STEM education to prepare current and future workforces. Schools in the UAE ought to prepare and motivate the students to join STEM careers. This study investigates stakeholder perceptions regarding STEM best practice in the UAE towards developing a STEM model. The data from this study in the UAE revealed that STEM practices are not common and require significant instruction for implementation. The recommendations of this study form a basis for establishing an effective STEM model in the UAE.